Nested polymerase chain reaction assay for the detection of B19 parvovirus DNA in human immunodeficiency virus patients - Musiani, M; Azzi, A; Zerbini, M; Gibellini, D; Venturoli, S; Zakrzewska, K; Re, M C; Gentilomi, G; Gallinella, G; La Placa, M (Journal of medical virology, 1993)
Persistent B19 parvovirus infection has been recognized in immunocompromised patients, often occurring with a low-titer viremia. In this study, nested polymerase chain reaction (PCR) for the detection of B19 parvovirus DNA was carried out on the sera of 49 human immunodeficiency virus (HIV)-1-seropositive patients, negative for the detection of B19 DNA at dot blot hybridization assay and with different values of serum anti-B19 IgM (27 patients proved positive and 22 negative). Of the 49 HIV-seropositive samples tested by nested PCR, seven were positive for the detection of B19 DNA. All seven belonged to the group of subjects seropositive for specific anti-B19 IgM. The study shows that, in the presence of specific B19 IgM, circulating virus may still be present but can be detected only by PCR. In that B19 infection can occur with low-titer viremia in immunocompromised patients, PCR may be the only method for virus detection.